2017
DOI: 10.1371/journal.pone.0181397
|View full text |Cite
|
Sign up to set email alerts
|

Including irrigation in niche modelling of the invasive wasp Vespula germanica (Fabricius) improves model fit to predict potential for further spread

Abstract: The European wasp, Vespula germanica (Fabricius) (Hymenoptera: Vespidae), is of Palaearctic origin, being native to Europe, northern Africa and Asia, and introduced into North America, Chile, Argentina, Iceland, Ascension Island, South Africa, Australia and New Zealand. Due to its polyphagous nature and scavenging behaviour, V. germanica threatens agriculture and silviculture, and negatively affects biodiversity, while its aggressive nature and venomous sting pose a health risk to humans. In areas with warmer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…As in previous work where irrigation is explicitly considered as having a mitigating influence on the distribution of a species [2932], we provide maps of the projected distribution of P . fijiensis under a natural rainfall scenario and as a composite of both the natural rainfall scenario and the 5 mm day -1 rainfall scenario.…”
Section: Methodsmentioning
confidence: 99%
“…As in previous work where irrigation is explicitly considered as having a mitigating influence on the distribution of a species [2932], we provide maps of the projected distribution of P . fijiensis under a natural rainfall scenario and as a composite of both the natural rainfall scenario and the 5 mm day -1 rainfall scenario.…”
Section: Methodsmentioning
confidence: 99%
“…Increasing temperatures may also lead to an increase in crop water demand resulting in an expanding area requiring irrigation during summer months, especially in southern and central Europe (EEA 2017;Wada et al 2013). For the invasive wasp, Vespula germanica (Hymenoptera: Vespidae), it was shown that including an irrigation scenario into CLIMEX significantly improved the model fit between present and estimated distribution (de Villiers et al 2017). Similarly, the use of irrigation systems may reduce the potential dry stress of H. halys during summer months, particularly in southern Switzerland, where irrigation is common practise.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to our results on the solitary I. mexicana , in social Hymenoptera niche shift after invasion seems more common. Indeed, a variety of niche shift patterns were observed in the invasive bumblebee Bombus terrestris (L.), in the invasive wasps Vespa velutina Lepeletier and Vespula germanica (Fabricius) and in most of the invasive ants studied so far [ 36 , 37 , 39 , 62 , 63 ]. Interestingly, the only other investigated alien solitary aculeate, the bee Anthidium manicatum (L.), also showed some degree of niche shift, particularly in the southern part of its invaded range (South America) [ 38 ].…”
Section: Discussionmentioning
confidence: 99%